Employment of chiral columns with superficially porous particles in chiral separations of cobalt bis (dicarbollide) and nido-7,8-C2 B9 H12 (1-) derivatives - Horáček, Ondřej; Dhaubhadel, Umang; Holub, Josef; Grüner, Bohumír; Armstrong, Daniel W; Kučera, Radim (Chirality, 2023)
Derivatives of the nido-7,8-C2 B9 H12 (1-) (dicarbollide ion) and [3,3'-Co-(1,2-C2 B9 H11 )2 ](1-) cobalt sandwich (COSAN) ion represent groups of extremely chemically and thermally stable abiotic compounds. They are being investigated in many research areas, that is, medicinal chemistry, material sciences, analytical chemistry, and electrochemistry. The chirality of these compounds remains still grossly overlooked, what is also reflected in limited number of reports on their chiral separations. Continued progress depends on reliable, fast, and cost-effective methods for such separations. Recently, chiral separations of COSAN derivatives were achieved in liquid chromatography and supercritical fluid chromatography. Only five anionic derivatives of nido-7,8-C2 B9 H12 (1-) were successfully enantioseparated in liquid chromatography. Efforts to separate anionic nido-7,8-C2 B9 H12 (1-) in supercritical chromatography have failed, and only a few dicarbollide ions were separated using liquid chromatography. Generally, all chiral separations in liquid chromatography took about 30 min. Herein, we identify a versatile column capable of separating both COSAN and nido-7,8-C2 B9 H12 (1-) derivatives and achieve faster analyses times employing commercially available superficially porous chiral stationary phases. The semisynthetic hydroxypropyl β-cyclodextrin-based column (CDShell-RSP) is identified as the column of choice from the tested columns by separating 19 of 27 compounds from each structural motifs tested mainly in less than 10 min. The dihydroxyalkyl, oxygen-bridged hydroxyalkyl, and bisphenylene-bridged COSAN derivatives were baseline separated in less than 5 min exceeding the results of supercritical fluid chromatography. Methods developed herein will aid synthetic chemists without the possession of a supercritical fluid chromatograph to achieve fast chiral separations of COSAN and derivatives of nido-7,8-C2 B9 H12 (1-) on a common liquid chromatograph without the need of dedicated instrumentation.
Keywords: chiral separations; cobalt bis (dicarbollides); cyclodextrin; superficially porous particles; carboranes; vancomycin; nido-carboranes